Increasing timber and declining live plant diversity and volumes in global trade from 2000 to 2020 - Alireza Naqinezhad; Oscar Morton; David P. Edwards (Communications Earth & Environment)
Abstract Plants are a vast, lucrative portion of global wildlife trade and the most speciose clade listed under the Convention on International Trade in Endangered Species of Wild Fauna and Flora-CITES. Here we used the CITES Trade Database and >420,000 records between 2000 and 2020 and assessed the diversity and volume of wild-sourced CITES-listed plants across space and time. Between 2000–2020, over 8.4 million cubic metres of timber, 197 million individual live plants, and 4.6 million kilograms of plant products were traded under CITES, comprising 53, 765, and 74 species, respectively. Most species are traded between key exporter and importer nations, especially China, USA, and Europe. Total diversity of timber species and volumes increased over time, whereas live diversity declined, and product diversity and mass fluctuated uncertainly. Most species were not evaluated by the International Union for the Conservation of Nature (IUCN) Red List when first traded, with high volumes of timber and products concentrated among threatened taxa. The high prevalence of poorly understood species necessitates enhanced rigour in ensuring sustainable CITES trade.